2014
DOI: 10.1021/jf501710u
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study To Explore Differences in Mycotoxin Patterns from Agro-ecological Regions through Maize, Peanut, and Cassava Products: A Case Study, Cameroon

Abstract: A total of 420 samples were collected from agrarian households. Whereas 51% (215/420) of the samples were contaminated with one or more toxins, the contamination rates for maize, peanut, and cassava products were 74, 62, and 24%, respectively. The fumonisins (20-5412 μg/kg), aflatoxin B1 (6-645 μg/kg), roquefortine C (1-181 μg/kg), and deoxynivalenol (27-3842 μg/kg) were the most prevalent contaminants in maize. For peanut samples, aflatoxin B1 (6-125 μg/kg) and ochratoxin A (0.3-12 μg/kg) were the main contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 37 publications
5
27
1
Order By: Relevance
“…Although there has been a gradual improvement, sub-Saharan Africa has been persistently ranked highest in human undernourishment worldwide with rates estimated between 31% in and 25% in 2011-2013(FAO, IFAD and WFP, 2013. Given the clear evidence of food shortage and high incidence of mycotoxin in food in Africa (Matumba et al, 2014;Adetunji, et al, 2014;Ediage et al, 2014;Mohale et al, 2013;Matumba et al, 2013;Lewis et al, 1995), is there any room for reaching a compromise between achieving food sufficiency and food safety in Africa? …”
Section: Toxicological Data On Mycotoxinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there has been a gradual improvement, sub-Saharan Africa has been persistently ranked highest in human undernourishment worldwide with rates estimated between 31% in and 25% in 2011-2013(FAO, IFAD and WFP, 2013. Given the clear evidence of food shortage and high incidence of mycotoxin in food in Africa (Matumba et al, 2014;Adetunji, et al, 2014;Ediage et al, 2014;Mohale et al, 2013;Matumba et al, 2013;Lewis et al, 1995), is there any room for reaching a compromise between achieving food sufficiency and food safety in Africa? …”
Section: Toxicological Data On Mycotoxinsmentioning
confidence: 99%
“…Based on available occurrence data on these mycotoxins(Doko et al, 1996; Bankole et al, 2013;Mohale et al, 2013;Adetunji et al, 2014 ;Ediage et al, 2014;Matumba et al, 2014a), the above calculated maximum limit would seriously exacerbate starvation in subSaharan Africa if enforced. Perhaps what would make it more complicated is that the climate inDownloaded by [New York University] at 06:52 17 July 2015…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In soil consisting of fungal biocatalysts of diferent origins, scientiic evidence seems to indicate that agricultural produce appears to be susceptible to spoilage due to substrate availability, which results in the proliferation of microbial spoilage organisms [32,33]. It has also been reported that fruit or produce has trace elements, such as Ca, Na, K and Zn, and low relative molecular weight hydrocarbons, including proteins and moisture, providing conditions which facilitate microbial growth and thus spoilage [34,35].…”
Section: Biological Reduction Of Cyanogensmentioning
confidence: 99%